1990
DOI: 10.1084/jem.172.4.1043
|View full text |Cite
|
Sign up to set email alerts
|

Genetic basis of viral persistence: single amino acid change in the viral glycoprotein affects ability of lymphocytic choriomeningitis virus to persist in adult mice.

Abstract: SummaryThis study has identified a single amino acid change in the viral glycoprotein that profoundly affects the ability of lymphocytic choriomeningitis virus (LCMV) to persist in its natural host . Adult immunocompetent mice infected with a variant--of the Armstrong strain, spleen isolate clone 13 (svA/svA), harbor virus for several months and exhibit suppressed T cell responses . In contrast, adult mice infected with a reassortant virus (svA/wtA) that contains the L segment of the spleen variant and the S s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
112
0
1

Year Published

1992
1992
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 114 publications
(116 citation statements)
references
References 18 publications
3
112
0
1
Order By: Relevance
“…Previous reports have suggested that functional inactivation or down-modulation of immune responses during chronic infection are critical for host survival (33)(34)(35). When previously uninfected adult mice are infected with LCMV clone 13 i.v., the virus replicates and disseminates rapidly (36). It can persist in the serum for up to 100 days, and remains indefinitely in some tissues.…”
Section: Chronic Infection Results In Increased Mortality In Cd43mentioning
confidence: 99%
“…Previous reports have suggested that functional inactivation or down-modulation of immune responses during chronic infection are critical for host survival (33)(34)(35). When previously uninfected adult mice are infected with LCMV clone 13 i.v., the virus replicates and disseminates rapidly (36). It can persist in the serum for up to 100 days, and remains indefinitely in some tissues.…”
Section: Chronic Infection Results In Increased Mortality In Cd43mentioning
confidence: 99%
“…Infected animals are not able to clear the infection, and virus titer is high in all tissues (19). Although T cell-mediated immunopathology is observed in these mice, mortality is rarely seen (25).…”
Section: Discussionmentioning
confidence: 99%
“…We have previously reported that infection of adult mice with LCMV clone 13 results in chronic infection associated with susceptibility to opportunistic histoplasmosis (4,19). Mice infected with this viral isolate are unable to mount an effective immune response against Histoplasma and succumb to a sublethal dose of the fungus.…”
Section: Mice With Chronic Viral Infection Are Susceptible To Opportumentioning
confidence: 99%
“…Effector and memory antigen-specific CD8 T cells were identified and purified by Fluorescence Activated Cell Sorting (FACS) using H-2D b tetramers bound to LCMV peptide GP33-41 conjugated to a fluorophore, along with CD8, CD44, CD127, Klrg1 and CD62L-fluorophore conjugated antibodies as previously described. 11,14,25,26 . To generate LCMV-specific CD8 T cell chimeras, transgenic P14 CD8 T cells with an engineered TCR that recognize the epitope GP33-41 of LCMV were harvested from naïve P14 TCR transgenic mice and adoptively transferred intravenously to C57BL/6 mice (cell# / mouse is specified in the figure legend) 11,2729 .…”
Section: Methodsmentioning
confidence: 99%